2015
DOI: 10.4269/ajtmh.14-0207
|View full text |Cite
|
Sign up to set email alerts
|

Mosquitoes of Anopheles hyrcanus (Diptera, Culicidae) Group: Species Diagnostic and Phylogenetic Relationships

Abstract: Abstract. Herein, we report the results of study of Anopheles species in Primorsk and Khabarovsk regions of Russia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The An. hyrcanus group is a widespread species group involved in the transmission of P. vivax and P. falciparum in Europe and Asia [ 101 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…The An. hyrcanus group is a widespread species group involved in the transmission of P. vivax and P. falciparum in Europe and Asia [ 101 , 102 ].…”
Section: Resultsmentioning
confidence: 99%
“…In molecular biological study of mosquitoes, it is reported recently that the mean intraspecific variations were less than 2% divergence (Kumar et al, 2007;Taira et al, 2012;Khrabrova et al, 2015). The mean intraspecific variations of 35 species including the medically important vector species of Anopheles, Aedes and Culex showed a less than 2% ranged with 0 1.5% divergences, but higher divergences of more than 2% were detected in Aedes aureostriatus okinawanus Bohart (2.2%) and Culex hayashii ryukyuanus Tanaka et al (3.3%) in the Ryukyu Archipelago, Japan (Taira et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…kleini compared to An. sinensis [ 40 , 41 ]. This may, in part, account for the higher numbers of malaria cases that continue to be reported from the DPRK [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, WHO in both the 2011 and 2015 malaria report continues to indicate that An. sinensis is the primary mosquito near the DMZ where malaria is transmitted, even though there is data to refute this supposition [ 7 , 11 , 12 , 35 , 37 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%